Case report: Long-term response to a combination of immune checkpoint inhibitors as a single treatment for multiple synchronous cancers: a case study - Ghammem, Nour; Bischoff, Herve; Chiappa, Pascale; Somme, Laura; Moinard-Butot, Fabien (Frontiers in Immunology, 2024)
IntroductionImmune checkpoint inhibitors (ICIs) have revolutionized cancer therapy by enhancing the antitumor immune response. This case describes an 80-year-old male with synchronous multiple primary malignancies (MPMs), including lung metastatic hepatocellular carcinoma (HCC), and non-small cell lung carcinoma (NSCLC), and brain metastatic urothelial carcinoma, who was treated with dual ICI therapy.Case presentationThe patient, with a history of diabetes, hypertension, dyslipidaemia, well-differentiated neuroendocrine duodenal tumors and micronodular exogenous cirrhosis (Child-Pugh class A), presented with a non-invasive bladder carcinoma (pT1N0M0) resected endoscopically in December 2022. Incidentally discovered hepatic and pulmonary tumors were confirmed as primary HCC and squamous cell carcinoma of the lung (cT1bN0M0, PD-L1 expression 100%), respectively. Due to the rapid progression of pulmonary metastases secondary to HCC, dual ICI therapy (durvalumab and tremelimumab) was initiated, resulting in a partial response (>30%) according to RECISTv1.1 criteria in pulmonary and hepatic lesions. After one year of ICI therapy, cerebellar syndrome due to secondary brain lesions emerged, which was confirmed as urothelial metastases. Surgical resection of the symptomatic cerebral metastases was completed with cerebral radiotherapy, and ICIs were continued. The patient is still receiving dual ICIs.DiscussionThis case highlights the crucial role of ICIs in treating MPMs. The patient’s favourable response suggests the importance of PD-L1 expression as a predictive biomarker.ConclusionThis rare case showed dual ICI therapy efficacy across multiple malignancies. Effective multidisciplinary collaboration and biomarker evaluation are crucial for managing such complex cases.